The testing of atomic absorption sources - Pospíšilová, Radka; Černohorský, Tomáš (Univerzita Pardubice, 1996)
The study was undertaken to compare the light sources of atomic absorption spectrometry for flame and furnace analysis. The hollow cathode lamps and boosted discharge lamps for determination of Se, As, Cd and Pb were tested. The main analytical characteristics as baseline noise, sensitivity, detection limits and linearity of calibration curves were measured. The significant gains in measurements of noise, sensitivity and linearity of calibration for Cd and Pb for discharge boosted lamps were observed.